2021
DOI: 10.3390/ani11051474
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Activity of Urban Bats Populations in Temperate Climate Zone—A Case Study from Southern Poland

Abstract: Municipal greenery can mitigate the negative impact of urbanization on biodiversity, including bats, by providing a migration corridor, food base and roosts. Our study aimed to evaluate the species composition and diversity, test the differences in activity between seasons, and identify the atmospheric conditions influencing the bats’ activity in the Planty Park (Cracow). Fieldworks were conducted in 2016 and 2017. We recorded 10 species, two new for this part of Poland: the Kuhl’s pipistrelle (Pipistrellus ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Eptesicus serotinus and Vespertilio murinus were con rmed only from single locations. Nyctalus leisleri and Eptesicus nilssoni were not con rmed during research in the city centre (Kohyt et al 2021). Research in Brno (Gaisler et al 1998) showed that the highest N. noctula activity was recorded in riverine environments, while E. serotinus was found the least frequently in this environment (it was most common in the old outskirts .…”
Section: Occurrence Seasonal Activity and Environmental Preferences O...mentioning
confidence: 90%
“…Eptesicus serotinus and Vespertilio murinus were con rmed only from single locations. Nyctalus leisleri and Eptesicus nilssoni were not con rmed during research in the city centre (Kohyt et al 2021). Research in Brno (Gaisler et al 1998) showed that the highest N. noctula activity was recorded in riverine environments, while E. serotinus was found the least frequently in this environment (it was most common in the old outskirts .…”
Section: Occurrence Seasonal Activity and Environmental Preferences O...mentioning
confidence: 90%
“…Yearly and seasonal patterns in temperature and precipitation, referred to in biogeographic modelling as bioclimatic factors or predictors, are known to influence behaviour and life history in bats around the world (Conenna et al., 2019 ; Gorman et al., 2021 ; Kohyt et al., 2021 ; Weinberg et al., 2022 ). To capture these conditions and test the hypothesis that macroclimatic effects can determine occurrence of bats, the 19 standard current bioclimatic predictor variables were sourced at 2.5 arc‐minute resolution from the WorldClim v2.1 database for the period of 1970–2000 (Fick & Hijmans, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Yearly and seasonal patterns in temperature and precipitation are known to influence behaviour and life history in bats around the world (Conenna et al, 2019;Gorman et al, 2021;Kohyt et al, 2021;Weinberg et al, 2022). To capture these conditions and test the hypothesis that macroclimatic effects can determine occurrence of bats, the 19 standard current bioclimatic variables were sourced at 2.5 arc-minute resolution from the WorldClim v2.1 database for the period of 1970 to 2000 (Fick & Hijmans, 2017).…”
Section: Bioclimatic Variablesmentioning
confidence: 99%